A PANDEMI COVID19 DAN IMPLEMENTASI PEMBELAJARAN ONLINE DI SDIT PERSIS CIGANITRI - Naih Nurjanah naih; Imas Nursanti Imas (Institut Agama Islam Persis Bandung, 2022)
This article discusses the covid19 pandemic outbreak that has occurred throughout the world, especially in Indonesia, which has implications for several government regulations and policies in various lines of social movement, especially in the field of education, one of which is schools. The teaching and learning process during the pandemic is carried out at home through distance learning or known offline through various media platforms or information technology devices such as E-learning, Quizzis, Google Classroom, Google Meet, Whatsapp, and others. The use of these devices has been applied at SDIT Persis Ciganitri, especially in the subjects that the author is researching, namely Islamic Religious Education (PAI). The research method used in this study is a qualitative approach while the type of this research method is descriptive. Aims to obtain in-depth and comprehensive information about the implementation of online learning on PAI subjects at SD Islam Terpadu Persis. As a result, the PAI learning process takes place using an E-learning strategy with the application of blended learning models such as lectures, exercises, assignments and demonstrations. There are three evaluation programs implemented, namely an assessment at the end of learning activities in the form of structured assignments and questions and answers, daily assessments carried out when one theme or KI/KD has been implemented, and end-of-semester and year-end assessments which are carried out at the end of each semester using google forms. Based on interviews and observations with schools, especially principals and PAI teachers, online learning is not without obstacles. There are supporting and inhibiting factors including teaching and learning activities that continue to run with the support of technological devices, but poor networks, large quotas, no parental guidance role, and the mentality of children who are not ready to learn online are the biggest obstacles in teaching and learning activities at home. Keywords: pandemic covid, PAI, SDIT Persis, online learning